Expression of tolerogenic potential-representing markers on clinical-grade therapeutic dendritic cell-based cancer vaccines - Dobrovolskienė, Neringa T.; Strioga, Marius M.; Liudkevičienė, Regina; Petraitis, Tadas; Darinskas, Adas; Pašukonienė, Vita; Gudlevičienė, Živilė (Acta medica Lituanica, 2014)
Background. Currently a particular interest is given to specific active cancer immunotherapy (therapeutic cancer vaccination) strategies such as treatment with specially “educated” autologous dendritic cells (DCs). The purpose of these vaccines is to enhance antitumor immune responses against the existing tumor. DC vaccines are composed of tumor antigen-loaded mature DCs, which are produced for each cancer patient individually. However, recent data indicate that there are at least two types of mature DCs  –  immunogenic, which activate antitumor immune responses, and tolerogenic, which suppress immune responses, thereby interfering with effector mechanisms of protective antitumor immunity. Hence, the aim of our study was to assess the expression of immunogenic and tolerogenic potential-representing markers on the surface of therapeutic DC vaccines generated using two different maturation approaches. Materials and methods. Two different DC maturation approaches were investigated: Cocktail 1, composed of lipopolysaccharide (200 ng/ mL) and interferon-γ (50  ng/mL), and Cocktail  2, composed of IL1β (10  ng/mL), IL-6 (10  ng/mL), TNF-α (10  ng/mL), PGE2 (1  μg/mL). Secretion of two basic cytokines – the immunostimulatory IL-12p70 and the immunosuppressive IL-10 – has also been investigated. Results. We show that a subset of immature DCs expressed tolerogenic markers. Importantly their expression profile considerably differed on mature DCs, depending on the maturation approach used. Conclusions. In particular, our results indicate that Cocktail  1 is superior to Cocktail  2 for the production of clinical-grade therapeutic cancer DC vaccines, both in terms of immunophenotypical attributes of DC tolerogenicity and their cytokine secretory profile.
Keywords: cancer immunotherapy; dendritic cell vaccine; immunogenic dendritic cells; tolerogenic dendritic cells